2021
DOI: 10.1093/geront/gnab180
|View full text |Cite
|
Sign up to set email alerts
|

Toward Responsible Artificial Intelligence in Long-Term Care: A Scoping Review on Practical Approaches

Abstract: Background and Objectives Artificial intelligence (AI) is widely positioned to become a key element of intelligent technologies used in the long-term care (LTC) for older adults. The increasing relevance and adoption of AI has encouraged debate over the societal and ethical implications of introducing and scaling AI. This scoping review investigates how the design and implementation of AI technologies in LTC is addressed responsibly: so called responsible innovation (RI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 77 publications
3
14
0
Order By: Relevance
“…Technologies to support older adults and their caregivers at home is an area of strong growth for design. Policy makers, providers, and family caregivers are looking to technological solutions and investing in artificial intelligence (AI) and other technologies that monitor activity and safety of older adults, with a particular focus on Alzheimer’s disease and related dementias (e.g., the AAL Joint Platform of the European Union and AGE-WELL Initiative in Canada) [ 25 , 69 , 91 , 127 , 129 , 138 ]. In the U.S., health care payment systems including Medicaid are now beginning to cover a range of technologies that have remote monitoring functions [ 17 , 28 ], foretelling significant growth as lack of third party reimbursement had impeded startups in the aging space [ 19 , 129 ].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Technologies to support older adults and their caregivers at home is an area of strong growth for design. Policy makers, providers, and family caregivers are looking to technological solutions and investing in artificial intelligence (AI) and other technologies that monitor activity and safety of older adults, with a particular focus on Alzheimer’s disease and related dementias (e.g., the AAL Joint Platform of the European Union and AGE-WELL Initiative in Canada) [ 25 , 69 , 91 , 127 , 129 , 138 ]. In the U.S., health care payment systems including Medicaid are now beginning to cover a range of technologies that have remote monitoring functions [ 17 , 28 ], foretelling significant growth as lack of third party reimbursement had impeded startups in the aging space [ 19 , 129 ].…”
Section: Background and Related Workmentioning
confidence: 99%
“…The burden of decision making about care without knowing that person’s preferences is also a source of stress for care partners ( Horowitz et al, 2004 ; Whitlatch et al, 2009 ). For these reasons, researchers have identified the need to educate families and people living with dementia about the technologies’ risks and benefits in a way that is accessible, clear, and meaningful to them ( Berridge et al, 2021 ; Lukkien et al, 2021 ; Meiland et al, 2017 ; Robillard et al, 2018 ; Thorstensen, 2018 ).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…However, current guidelines are generally highly abstract and leave much room for interpretation as to how these principles can be practically applied and contextualized to specific technologies like AI-DSSs and in specific contexts such as LTC [27,28]. While scholars recognize the importance of a more context-specific conceptualization of these principles, multiple literature reviews have shown that only few studies specify practical approaches to responsible AI innovation for specific application domains, and this is especially true for applications of AI in LTC [6,8,29,30].…”
Section: Introductionmentioning
confidence: 99%